2016
DOI: 10.23953/cloud.ijanhs.137
|View full text |Cite
|
Sign up to set email alerts
|

Quality Nutrition Education and Its Impact on Haemoglobin Levels of School Pupils of Muranga County, Kenya

Abstract: Anaemia can dramatically affect school children with adverse impact on their cognitive development and school performance. Nutrition education has not been given the priority it deserves in primary schools due to the busy school curriculum although it is concerned with changing an individual's behavior. It is in this light that this study was designed. The main objective of this study was to evaluate the effects of three main nutrition education facilitators on nutrition knowledge among primary schools childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
4
1
0
Order By: Relevance
“…These results come in agreement with the results presented by Kumari and Dubey in Rajasthan (9.3 vs. 13.83) [26]. Other studies also showed comparable results in Kenya (9.87 vs. 39.29), Selangor and Kuala Lumpur (48.3 vs. 55), and Ghana (8.3 vs. 21.6) [27], [28], [29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results come in agreement with the results presented by Kumari and Dubey in Rajasthan (9.3 vs. 13.83) [26]. Other studies also showed comparable results in Kenya (9.87 vs. 39.29), Selangor and Kuala Lumpur (48.3 vs. 55), and Ghana (8.3 vs. 21.6) [27], [28], [29].…”
Section: Discussionsupporting
confidence: 91%
“…Analysis of the 24-h dietary recall of participants in this study revealed a significant increase in the mean daily intake of protein, Vitamin A, calcium, Iron, and zinc post-intervention and this comes in concordance with a study done in Kenya [27]. Another study conducted in Indonesia among 83 female adolescents aged 16-18 years students of the Hidayatullah Arrohmah Islamic Boarding School Malang showed that before the intervention 66% of respondents had low protein intake.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, respondents indicated that dry land arrowroots are tastier and filling and their large yield size gives ample food for the family. The study results correspond with Gitau et al, (2016) who argues that scarcity of minerals and vitamins associated with hidden hunger has significant problems to health and wellness. The respondents' commented that dry land arrowroots, tastes better and motivates production and consumption.…”
Section: Resultssupporting
confidence: 88%
“…In addition, fast maturing food crops are essential for food security and fighting hidden hunger. This agreed with Gitau et al, (2016) who argues that hidden hunger is a significant problem where people consume food to fight hunger at the expense of nutritional value. Children consuming biofortified crops experienced fewer cases of anemia's among school going children from pre intervention and post intervention with fortified food crops demonstrate better health and nutritional security.…”
Section: Discussionsupporting
confidence: 57%
“…The continued farming of staple foods has left vast soils experiencing degradation. Gitau et al (2016) in a study reported increasing cases of anemia and malnutrition among school going children in Kandara. The study revealed cases of hidden hunger among school going children associated with lack of diet diversification.…”
Section: Introductionmentioning
confidence: 98%